UJI DAYA HAMBAT EKSTRAK DAUN LALUMPA (Melastoma malabathricum L.) TERHADAP PERTUMBUHAN BAKTERI Vibrio cholerae dan Staphylococcus aureus - Mutmainnah Mutmainnah; Wahyu Harso; Orryani Lambui (Biology Department, Mathematics and natural science, Tadulako University, 2019)
Vibrio cholera and Staphylococcus aureus are a gram negative and a gram positive bacteria respectively. Both of them can cause diseaces in human. They have differences in their cell wall composition. Differences in both bacteria in the resistance to antibacterial compounds interesting to learn. The aim of this study was to observe inhibition of Melastoma malabathricum leave extract to the growth of V. Cholera and S. aureus. The study was conducted with Completely Randomized Design. The treatment was tested with 10%, 20%, 40%, 60%, 80% of leave extract concentration. Amoxicillin 2% and Na-CMC 1% were also treated as positif and negative control. Each treatments was repeated three times. Extract was obtained by maceration method. Extract was injected on bacterial growth medium by well diffusion method. The result showed that increasing extract concentration increased inhibition of growth to both bacteria. V. cholera tended to be more resistant than S. aureus.